Pedagogical Possibilities of Teaching Folk Oral Creativity Samples on the Basis of Interdisciplinary Integration in Primary Classes - Aziza Shikhnazarovna Jabborova (International Journal on Integrated Education, 2026)
In this article, we look at how teachers can use folk oral works - proverbs, riddles, fairy tales, and folk songs - across several school subjects in primary grades. Instead of keeping these materials only in native language classes, we tested what happens when teachers bring them into math, science, music, and art lessons. We ran a two-year trial with 240 students in schools across Bukhara region. Our results showed that students in the test group did better than their peers in learning new ideas, thinking more freely, and holding onto what they learned. We argue that folk oral works, when teachers use them in more than one subject, become a much stronger teaching tool than they are under the usual approach.